Rotational rifting in Antarctica - V. P. Kobolev; Yu. P. Orovetsky (Ukrainian Antarctic Journal, 2004)
The rotational rifting as a consequence of the rotational Earth’s movement is accompanied by the formation of the planetary equatorial deep separations. Their repeated and no simultaneous intersections of the Antarctica ancient mother crystal had led to the origin of the large-scale spreading area with the synchronous formation of the deep multimagmatogene. This had been completed by the continent formation that transformed into the ancient platform.